2008
DOI: 10.1007/s12221-008-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cotton fabric treated with an amino-terminated hyperbranched polymer

Abstract: An amino-terminated hyperbranched polymer (HBP-NH 2 ), synthesized from methyl acrylate and diethylene triamine by polycondensation, was applied to treat cotton samples by a pad-dry-cure method. Physical properties, salt-free dyeability, antimicrobial activity, and antiultraviolet property of the treated cotton samples were tested. The crystallinity and mechanical properties, including breaking strength, breaking elongation, and Young's modulus of the treated cotton fibers, increased slightly in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This is of particular interest because the treatment with HBP can improve the ultraviolet protection property of PET fabrics. Such observation on cotton fabrics has already been reported in a publication …”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This is of particular interest because the treatment with HBP can improve the ultraviolet protection property of PET fabrics. Such observation on cotton fabrics has already been reported in a publication …”
Section: Resultssupporting
confidence: 72%
“…On the subject of cotton fabrics, the amino‐terminated hyperbranched polymers can act as a salt‐free dyeing auxiliary . Furthermore, it has shown that the application of the HBPs to cotton fabrics can reduce UV transmission and impart antibacterial properties …”
Section: Introductionmentioning
confidence: 99%
“…The hyperbranched polymer with amino terminal groups, HBPA, was synthesized by condensation polymerization of AB 2 ‐type monomers, details of which have been described elsewhere . Briefly, 52 mL of methyl acrylate were blended with 43 mL of diethylenetriamine in 100 mL of methanol for 6 h in an ice‐water bath.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, an amino-hyperbranched polymer (HSDA) was synthesized. It was utilized to control synthesis of Ag and ZnO nanoparticles, and also served as a binder to impart and fix the nanoparticles on cellulose fabric to provide antimicrobial properties [19,20,21]. In this paper, amino-capped TiO 2 NPs were attempted to be synthesized by the sol-gel and hydrothermal method, using a mixture of tetrabutyl titanate (TBT)and amino polymers as a raw material.…”
Section: Introductionmentioning
confidence: 99%